Succesful fiscal adjustments: Does choice of fiscal instrument matter? - Steinar Holden; Nina Larsson Midthjell (University of Oslo, Department of Economics, 2013)
We examine fiscal adjustment episodes in 24 OECD countries in order to find how austerity affects debt and growth, and whether the choice of fiscal instrument matters for the results. Inuential existing studies argue that spending cuts are more likely to successfully reduce debt and enhance economic growth than tax increases. Our main innovations over these studies are to better account for initial conditions and to employ a novel and more precise measure of actual changes in fiscal policy. We find that whether a fiscal adjustment is successful in reducing debt depends on whether the adjustment was suffifficiently large to remove the budget deficit. We find no indication that it matters whether the adjustment is achieved via spending cuts or tax increases, and this conclusion holds also for the effect on economic growth.
Keywords: H2; H3; H5; H62; 330